Polska religijność w liczbach - Himniak, Agnieszka (Społeczeństwo, 2022)
Religion has a significant role in human life. It gives meaning to human actions, as well as social structures that people function within. Due to its community-related nature, religion also serve an important social and integrative function. Any human religious action with regard to sacrum introduce order and rhythm to human life, co- -creating the everyday reality. When speaking of religious actions and believers’ involvement in religion, we refer to religiousness that constitutes the main topic of this elaboration.